Mexico 50 Savoring 50-year Harmony: A Fushion of Malaysia-Mexico Delights - Kahirol Mohd Saleh,; Nik Mohammad Hasif Mat,; Andrew Kam Jia Yi,; Nor Lisa Sulaiman,; Rashila Ramli, (2025)
This publication, Malaysia-Mexico@50: Savoring 50 Years of Harmony – A Fusion of Malaysia-Mexico Delights, commemorates five decades of diplomatic relations between Malaysia and Mexico. It celebrates a long standing friendship built on mutual respect, cultural appreciation, and collaborative progress. The book highlights the role of academic institutions in strengthening bilateral ties, particularly the involvement of Universiti Kebangsaan Malaysia (UKM) through the establishment of the Center for Latin American Studies (iKAL) at the Institute of Malaysian and International Studies (IKMAS) in 2013. Since its establishment, iKAL has served as an important platform for fostering understanding of Latin American culture and society from an Asian perspective, including the publication of the Malay edition of Nueva Historia Mínima de México in 2016. The book also reflects the expanding academic collaboration between Malaysia and Mexico, with contributions from institutions such as Universiti Tun Hussein Onn Malaysia (UTHM), Universiti Poly-Tech Malaysia (UPTM), and the Universidad de Ixtlahuaca (UI CUI). Inspired by academic visits and culinary exchanges between both countries, particularly a collaborative gastronomy experience in 2023, this publication showcases the fusion of Malaysian and Mexican culinary traditions as a symbol of cultural exchange and friendship. Through educational cooperation, including student exchanges, joint research, and academic partnerships, Malaysia and Mexico continue to strengthen cross-cultural understanding and global engagement. This book serves not only as a reflection of past achievements but also as a celebration of the present and a hopeful vision for future collaboration between the two nations.